Putusan Praperadilan Yang Menyimpang Secara Fundamental - AMIR GIRI MURYAWAN (Scholar Center, 2021)
Pretrial hearing is designed for a simple issue, no more than to control administrative proceedings of criminal enforcement. This can be seen from the simplicity of the pretrial hearing concept in Article 77 of the Criminal Procedure Code. Demands for justice for suspects/defendant led to developments in the pretrial system. However, these developments have a negative side, resulting in idealized norms being modified in such a way as to meet sociological interests, which are not necessarily in line with their philosophical and juridical aspects. The most visible impact is that the Judicial Review against Article 77 of the Criminal Procedure Code results in broading the object of pretrial hearing that has serious implications for the procedure law. The problem in this research is whether the decision of pretrial in assessing the core issue of the case includes